2020
DOI: 10.3390/ani10091540
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Correlated Response in Two Lines of Rabbit Selected Divergently for Litter Size Environmental Variability

Abstract: A divergent selection experiment for environmental variance of litter size variance was carried out in rabbits over thirteen generations. The aim of this study was to evaluate the inflammatory response in the two lines of the experiment, in order to analyse the effect of selection on susceptibility to diseases after challenging to stressful situations, such as 24 h after the first delivery. A total of 78 females were used in this study, 39 from each line. The line selected for litter size heterogeneity (the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
6
16
0
Order By: Relevance
“…LPS increased the expression of LDLr at the mRNA level and intracellular cholesterol ester content. Previously, studies have shown that intracellular cholesterol accumulation could obstruct mitochondrial function [30] and increase sensitivity to inflammation [31], thus affecting negative feedback regulation of LDLr [32,33]. Ma et al also reproted that inflammation increased lipid accumulation in VSMCs by disrupting LDLr feedback regulation [34], which further supports our present findings.…”
Section: Furthermore Macrophage-derived Foam Cells Have Attracted Extensive Scholars' Attention Whilesupporting
confidence: 91%
“…LPS increased the expression of LDLr at the mRNA level and intracellular cholesterol ester content. Previously, studies have shown that intracellular cholesterol accumulation could obstruct mitochondrial function [30] and increase sensitivity to inflammation [31], thus affecting negative feedback regulation of LDLr [32,33]. Ma et al also reproted that inflammation increased lipid accumulation in VSMCs by disrupting LDLr feedback regulation [34], which further supports our present findings.…”
Section: Furthermore Macrophage-derived Foam Cells Have Attracted Extensive Scholars' Attention Whilesupporting
confidence: 91%
“…There were also differences in sensitivity to stress and diseases, which lowered the culling rate in the low line [ 11 ]. In this regard, the more homogeneous line coped better with environmental stressors such as infections and acute stress than the heterogeneous line which showed higher resilience [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hematological parameters provide valuable information on the health status of the animal. In the present study, the hematological profiles were within the range for healthy rabbits both at the beginning and end of the experiment and for both diets [ 18 , 23 ]. Levels of albumin, alkaline phosphatase, alanine aminotransferase, total bilirubin, total protein, globulin, glucose, creatinine, uric nitrogen and amylase are within the wide range of values reported in rabbits [ 18 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 77%
“…Following the blood sampling procedure described in [ 18 ], blood samples were collected into a tube with tripotassium ethylenediaminetetraacetic acid (K3-EDTA) at weeks 0 and 15. Hematological parameters such as white blood leukocyte count (WBC, 103/μL) and percentage of lymphocytes, neutrophils, monocytes, basophils and eosinophils were determined with the Abacus Junior Vet hematology analyzer (Diatron, Austria).…”
Section: Methodsmentioning
confidence: 99%